Process capability of high speed micro end-milling of Inconel 718 with minimum quantity lubrication - Abd. Rahman, Mohamed; Ali, Mohammad Yeakub; Rosli, Abdul Rahman Shah; Banu, Asfana (IOP Publishing, 2017)
The demand for micro-parts is expected to grow and micro-machining has been shown to be a viable manufacturing process to produce these products. These micro-products may be produced from hard-to-machine materials such as superalloys under little or no metal cutting fluids to reduce machining cost or drawbacks associated with health and environment. This project aims to investigate the capability of micro end-milling process of Inconel 718 with minimum quantity lubrication (MQL). Microtools DT-110 multi-process micro machine was used to machine 10 micro-channels with MQL and 10 more under dry condition while maintaining the same machining parameters. The width of the micro-channels was measured using digital microscope and used to determine the process capability indices, Cp and Cpk. QI Macros SPC for Excel was used to analyze the resultant machining data. The results indicated that micro end-milling process of Inconel 718 was not capable under both MQL and dry cutting conditions as indicated by the Cp values of less than 1.0. However, the use of MQL helped the process to be more stable and capable. Results obtained showed that the process variation was greatly reduced by using MQL in micro end-milling of Inconel 718.